ENT medical therapeutics in Portugal and doping - Cavilhas, Pedro (2009)
Objectives: Revision of substances and methods considered doping in the year of 2010 with identification of active principles commercialized in Portugal (made available by Infarmed - the Portuguese drug authority) and eventually used in ENT speciality and revision of the procedures to be taken by the ENT specialist in case of prescription to athletes.Materials and methods: Literature review.Results: Drugs important to ENT specialty,which are considered doping include: diuretics, plasma expanders, some stimulants (ephedrine, pseudoephedrine and sibutramine), glucocorticoisteroids (by mouth, IV and IM) and fl-2 agonists. Some substances although are not doping (were in the past and can be in the future) are monitored (bupropion, caffeine and phenylephrine). However it is allowed to prescribe forbidden substances, in justified cases, as long as adequate forms are filled.Conclusions: It is the duty of an athlete to inform the doctor of is condition of eligibility for antidoping control tests and it is the duty of the doctor, in the perspective of prescribing forbidden substances, either to ponder alternatives or to fill a Therapeutic Use Exemption